Peran Tokoh Adat Dalam Menyelesaikan Konflik Keluarga Akibat Perselingkuhan Dan Penelantaran Anak Di Desa Pantae - Kudu, Ruslan Firdaus; Wilhelmus, Bhisa Vitus; Dede, Ngongo (Law Faculty, Nusa Cendana University, 2025)
The problems that occur in the lives of Indonesian society, one of which is in Pantae Village, Biboki Selatan District, North Central Timor Regency is the case of infidelity and child neglect. The formulation of the problem this study is: the purpose of this study 1. To determine the role of traditional leaders in resolving family conflicts due to infidelity and child neglect in Pantae Village. 2. To determine the factors that influence the effectiveness of the role of traditional leaders in resolving the conflict. This study is an empirical legal research, namely research based on applicable laws and regulations and data obtained in the field regarding the role of traditional leaders in resolving family conflicts due to infidelity and child. The results of this study indicate that the role of traditional leaders in resolving family conflicts due to infidelity and child neglect that occurred in Pantae Village, namely, (1) Reporting (2) Listening to statements from witnesses and perpetrators (3) Deliberation (4) Decisions and peace processes (5) Determination of customary sanctions for perpetrators. Factors that influence the effectiveness of the role of traditional leaders in resolving the conflict are, (1) Factors of limited human resources (2) Factors of changing times (3) Economic factors (4) Factors of massive early marriage in society. So it can be concluded that if traditional leaders have reached a decision, then the decision is considered valid and final and has legal force that can be accepted by all parties involved.